The Effect of Using Music Classic (Mozart) towards Student Anxiety Before The Exams - Risa Yuspitasari; Rahmawati; Raudah Zaimah Dalimunthe (Journal of Family Sciences, 2020)
This research aimed to discover the level of anxiety in students before the exam and the effect of music classic (Mozart) to reduce such anxiety. The study was conducted at SMP Negeri 1 Ciruas with students with a high level of anxiety, which has been revealed from the results of the anxiety scale questionnaire using a purposive sampling technique with a total of 68 respondents. This research was used with an experimental method consisting of an experimental group and a control group. From the treatment, the results showed pre-test 12.55 in the high category and post-test 7.852 in the medium category. This shows changes in the results before and after the treatment is given. It can be concluded that the effect of the use of music (Mozart) can reduce student anxiety before the test.